2017
DOI: 10.25301/jpda.261.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Occlusal Incisal Tooth Wear and Its Influential Factors among Subjects Visiting a University Hospital in Pakistan

Abstract: ABSTRACT:INTRODUCTION: Tooth wear is a global problem that involves an irreversible, non-carious loss of dental hard tissues due to repetitive physical contacts or chemical dissolution. The objective of the study was to determine the frequency and influential factors of tooth wear among patients visiting AKUH dental clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
2
9
1
Order By: Relevance
“…Exposure to the risk factors with advancing age lead to more deteriorated condition overtime. This coincide with the outcomes of previous studies in other populations 3 . Oginni et al concluded that prevalence of tooth wear increased with the age of patients 13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Exposure to the risk factors with advancing age lead to more deteriorated condition overtime. This coincide with the outcomes of previous studies in other populations 3 . Oginni et al concluded that prevalence of tooth wear increased with the age of patients 13 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study out of 120 patients, 69 were male and 51 were female. Another study conducted in Karachi also found tooth wear more prevalent in male population 3 . Female population may have showed more concern about dental treatment and follow regular visits to dentist.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As tooth surface loss is multifactorial, therefore the abrasive effect of tooth brushing can cause a tooth surface loss. The present study reported that people using a brush with medium bristles (41.2%) in horizontal technique (69.2) % with medium force (40.4) % tend to have more tooth surface loss which shows a correlation with the study reported by Ahmed et al 32 that brushing with moderate type of brush (48.4) % shows relevant tooth surface loss. Another study reported by Mushtaq et al 33 also observed a substantial association between participants using different types of toothbrushes and hard tissue abrasive lesions was reported(p<0.05).…”
Section: Discussionsupporting
confidence: 85%
“…Kehua Q et al 21 in a study reported that there is an association between dentin hypersensitivity and age groups. Ali K et al 32 find abnormal tightening and bruxism with a significant relationship with tooth surface loss. The present study reported that only 7.6% experienced tooth surface loss due to tightening/ bruxism, while 45.2% experienced tooth surface loss due to chewing pan.…”
Section: Discussionmentioning
confidence: 99%